2016
DOI: 10.5755/j01.ee.27.4.15360
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Goodwill Impairment in the Baltic States

Abstract: International accounting standards provide recommendations that specify which factors should be taken into consideration prior to the determination of goodwill impairment; however, decisions on goodwill impairment disclosures are mainly conditioned by the influence of managers and other factors based on self-interests. Therefore, the objective of the article is to perform research on goodwill impairment managed by companies that are listed by the NASDAQ OMX Baltic Stock Exchange and to determine factors and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
8
1
Order By: Relevance
“…The mean difference in Lev between the two groups is 0.056, significant at the 1 % level. This finding coincides with the studies by the scientists Jahmani (2010) and Sapkauskiene et al (2016), which found that the more indebted companies are likely to disclose the goodwill impairment, and are likely to disclose larger amount of goodwill impairment. The mean difference in Loss_dum between the two groups is 0.202, significant at the 1 % level.…”
Section: Correlation Testsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean difference in Lev between the two groups is 0.056, significant at the 1 % level. This finding coincides with the studies by the scientists Jahmani (2010) and Sapkauskiene et al (2016), which found that the more indebted companies are likely to disclose the goodwill impairment, and are likely to disclose larger amount of goodwill impairment. The mean difference in Loss_dum between the two groups is 0.202, significant at the 1 % level.…”
Section: Correlation Testsupporting
confidence: 91%
“…But, the correlation coefficient between Lev and Imp is 0.09, positive significant at the 1% level . This finding is in contrary to the results of the studies carried out by Beatty & Weber (2006), Zang (2008), AbuGhazalech et al (2011, as well as Ramanna & Watts (2012), but coincides with studies carried out by Jahmani (2010) and Sapkauskiene et al (2016) .The correlation coefficient between Loss_dum and Imp is 0.47, significant at the 1 % level. This indicates that the loss of performance variable is positively correlated with the impaired continuous variable, and if the company has already lost, the manager will tend to recognize more goodwill impairment to carry out a "big bath".…”
Section: Descriptive Analysis Of Study Samplecontrasting
confidence: 57%
See 1 more Smart Citation
“…It seems to be the most representative way for researchers to measure the factors influencing write-offs. Many regression variants can be found in the data sample, for example, the ordinary least squares (OLS) regression model [28,29] and the probit model, whereby the dependent variable can only take two values to find the explanatory variables for the impairment decision [30]. To determine the impact of hypothesised drivers on the write-off decision, Garrod et al [31] estimated four separate logistic regressions for the companies included in the total sample.…”
Section: Data Sample Characteristicsmentioning
confidence: 99%
“…Hayn and Hughes [61] measured the impairment indicators in acquisitions. They intended to understand whether investors can predict goodwill impairment based on financial statements, and they assumed that their ability to do so is highly limited (as also assumed by Sapkauskiene et al [29], basically due to the quality of those statements. They also showed that the disclosure of the impairment is mainly delayed and taken after the entity has experienced a worse condition for a considerable period.…”
Section: Asset Impairment As An Opportunity For Earnings Managementmentioning
confidence: 99%